Planter un arbre en Israël : une forêt rédemptrice et mémorielle - Sylvie Friedman (Diasporas: Circulations, Migrations, Histoire)
All along Israel’s Zionist project, plants are called upon to play a role of mediation between the land dreamed of and the land walked upon, between biblical text and reality. National reinvestment built through plants that had already been known from the diapora, reorganized in scenes significant to Jewish memory and history. This filiational link between sacred text and landscape context led to a plantation practice considered as a mystical act of redemption of the land.